2020
DOI: 10.3389/fendo.2020.00385
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Estrogen Receptor: Rapid Effects on Hippocampal-Dependent Spatial Memory and Synaptic Plasticity

Abstract: In the hippocampus, estrogen regulates gene transcription linked to neuronal growth, neuroprotection, and the maintenance of memory function (1-3). The mechanism is likely to involve genomic regulation through classic estrogen receptor (ER) signaling cascades that influence transcription. Estrogens binding to classic nuclear ERs, alpha (ERα) and beta (ERβ), and have pleotropic effects on development, behavior, and neurophysiological functions, including synaptic plasticity and memory consolidation (4-7). In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…1-1 ). Based on the selective binding profiles of GPER agonist G-1 and antagonist G-15 (see Materials and Methods) and physiological studies in the field ( McCarthy, 2008 ; de Valdivia et al, 2017 ; Kumar and Foster, 2020 ), we initially tested the effects of G-1 alone at 100 n m and G-15 alone at 10 n m on the growth of cultured hippocampal and cortical neurons compared with neurons cultured in vehicle (0.1% DMSO). Our results showed that in hippocampal neurons G-1 alone significantly ( p < 0.01) increased average neurite outgrowth (μm), while G-15 alone had no effect ( p > 0.05) compared with vehicle (one-way ANOVA, F (2,638) = 18.46, p < 0.01; Vehicle: 52.4 ± 3.1, n = 264 cells; G-1: 78.1± 4.4, n = 180 cells; G15: 45.2 ± 4.1, n = 197 cells).…”
Section: Resultsmentioning
confidence: 99%
“…1-1 ). Based on the selective binding profiles of GPER agonist G-1 and antagonist G-15 (see Materials and Methods) and physiological studies in the field ( McCarthy, 2008 ; de Valdivia et al, 2017 ; Kumar and Foster, 2020 ), we initially tested the effects of G-1 alone at 100 n m and G-15 alone at 10 n m on the growth of cultured hippocampal and cortical neurons compared with neurons cultured in vehicle (0.1% DMSO). Our results showed that in hippocampal neurons G-1 alone significantly ( p < 0.01) increased average neurite outgrowth (μm), while G-15 alone had no effect ( p > 0.05) compared with vehicle (one-way ANOVA, F (2,638) = 18.46, p < 0.01; Vehicle: 52.4 ± 3.1, n = 264 cells; G-1: 78.1± 4.4, n = 180 cells; G15: 45.2 ± 4.1, n = 197 cells).…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiments have demonstrated that the memory consolidation effects observed after the administration of osanetant are dependent on the sexual maturity of the mouse [ 7 ], either male or female. Interestingly, given the involvement of sex hormones in the regulation of Nk3R activity on memory formation [ 7 ], estrogen GPCR has recently been shown to modulate hippocampal-dependent memory and long-term potentiation [ 45 ]. Although the Nk3R presents a significant number of heterodimers with AR in males and proestrus females, the Nk3R–GPER heterodimer appears quite more abundant than the rest, pointing to a possible explanation for the increased efficacy of Nk3R during high estradiol levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, non-genomic effects involve the indirect regulation of gene expression through a variety of intracellular signaling events. The G-protein coupled receptor (GPR)30, also known as G-protein coupled ER1, has been extensively investigated as a membrane ER that activates non-genomic estrogen signaling pathways in a variety of tissues (160). ERα is closely associated with endocrine sensitivity in breast cancer and is a significant mediator of the estrogen response in OC (161,162).…”
Section: Estrogenmentioning
confidence: 99%